Improving Students’ Conceptual Understanding Through Geogebra-Assisted “5E” Learning Cycle: Is It Effective? - Ni Nyoman Wulan Darma Putri; I Wayan Puja Astawa; I Made Ardana (Universitas Pendidikan Ganesha, 2021)
This study aims to investigate the effectiveness of GeoGebra-assisted 5E Learning Cycle model toward student’s understanding of mathematical concept with control of student’s prior knowledge. This study was a quasi-experiment with post-test only control group design. The population of the study was 324 ninth grader students where 81 of them were selected as sample through cluster random sampling technique. The data collected in this study were student’s mathematical prior knowledge obtained by giving objective tests before starting the learning process and data of student’s mathematical conceptual understanding obtained by giving an essay test at the end of learning process. The hypotheses were tested using t-test and one-way analysis of covariance test. The results showed that: the usage of GeoGebra-assisted 5E Learning Cycle Model has a positive impact toward student’s understanding of mathematical concept, where t = 2,977 and p = 0,002; the usage of GeoGebra-assisted 5E Learning Cycle Model has a positive impact toward student’s understanding of mathematical concept after the prior knowledge variable was controlled, where F = 31,880 and p = 0,000. The findings of this research implied that GeoGebra-assisted 5E Learning Cycle Model can be used as an alternative learning model in an effort to improve students' understanding of mathematical concepts.